2008
DOI: 10.1175/2007jtecha969.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Wind Field Inhomogeneities on Doppler Beam Swinging Revealed by an Imaging Radar

Abstract: In this work, the accuracy of the Doppler beam-swinging (DBS) technique for wind measurements is studied using an imaging radar-the turbulent eddy profiler (TEP) developed by the University of Massachusetts, with data collected in summer 2003. With up to 64 independent receivers, and using coherent radar imaging (CRI), several hundred partially independent beams can be formed simultaneously within the volume defined by the transmit beam. By selecting a subset of these beams, an unprecedented number of DBS conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 18 publications
2
14
0
Order By: Relevance
“…supporting and explaining results obtained by Cheong et al (2008), who have experimentally shown that the MSE or likewise the RMSE of the wind retrieval is significantly reduced by increasing the number of off-vertical beams in the Doppler beam-swinging technique in the presence of wind field inhomogeneities. Note, however, that for the vertical wind component only the random error can be reduced by an increase of N.…”
Section: Estimation Of the Retrieval Errorsupporting
confidence: 85%
“…supporting and explaining results obtained by Cheong et al (2008), who have experimentally shown that the MSE or likewise the RMSE of the wind retrieval is significantly reduced by increasing the number of off-vertical beams in the Doppler beam-swinging technique in the presence of wind field inhomogeneities. Note, however, that for the vertical wind component only the random error can be reduced by an increase of N.…”
Section: Estimation Of the Retrieval Errorsupporting
confidence: 85%
“…It is well known that the wind field is not always horizontally homogeneous Cheong et al, 2008), this is mainly due to convection, gravity waves or shear induced turbulence. Characteristic temporal and spatial scales for turbulence are T = 10 s and L = 1 m. For thermally induced convective processes we typically have T = 5 min and L = 500 m. Thus, with reference to a full DL scan lasting about 3 min and with a scanning circle having height dependent diameters d C of about d C ∼ 300 m at an altitude of ∼ 550 m and d C ∼ 5360 m at ∼ 10 km it is often the case that due to the occurrence of turbulent motions there are rapid wind fluctuations along the scanning circle and accordingly the assumption of a horizontally homogeneous wind field is not fulfilled.…”
Section: Test Of Horizontal Homogeneitymentioning
confidence: 99%
“…c Profile of the corrected signal-to-noise ratio SNR cor retrieved from the wind profiler measurements and derived PBL height (horizontal line) recorded on the 7 July 2010 at 1200 UTC and the frequency-domain steps (Ruffieux and Stübi 2001;Vaisala 2007). An important assumption is a homogeneous wind field over the beams' separation (Koscielny et al 1984;Cheong et al 2008), which cannot be fully guaranteed in the complex topography of the Alps.…”
Section: Wind Profilermentioning
confidence: 99%